Relationship between IgA vasculitis and prothrombotic risk factors: A prospective, case-control study - Cengiz Zeybek,; Ahmet Bolat,; Orhan Gürsel,; Bülent Hacıhamdioğlu,; Ahmet Emin Kürekçi, (Archives of Rheumatology, 2024)
Objectives: This study aimed to determine whether there are commonly occurring hematologic causes that may lead to thrombosis in patients recently diagnosed with immunoglobulin A vasculitis (IgAV). Patients and methods: The prospective study enrolled 107 pediatric patients diagnosed with IgAV and 98 healthy age- and sex-matched controls. Patients with IgAV who were treated at a single center between February 2016 and June 2022 were evaluated for the prevalence and clinical relevance of thrombophilic gene mutations and other prothrombotic risk factors, as well as coagulation test indices. The genotypes for common mutations in prothrombin (Pt) G20210A, factor V Leiden (FVL), and methylenetetrahydrofolate reductase (MTHFR) C677T were assessed. The coagulation assays, including Pt time and activated partial thromboplastin time, and the levels of fibrinogen, factor VIII, factor IX, and von Willebrand factor antigen were analyzed. Additionally, the levels of antithrombin, protein C, and free protein S were evaluated during the disease’s acute phase before initiation of anti-inflammatory drugs. Results: Seventeen of the 107 IgAV patients were excluded. Consequently, 90 children (36 males, 54 females; mean age: 10.2±3.2 years; range, 3 to 18 years) diagnosed with IgAV and 98 healthy children (45 males, 53 females; mean age: 9.7±3.8 years; range, 2 to 18 years) as a control group were analyzed. A statistical analysis found no significant difference between the groups in terms of indices of coagulation assays and other prothrombotic risk factors (p>0.05). The mutation frequencies of the Pt G20210A, FVL, and MTHFR C677T loci among IgAV patients were not significantly different from the control group (p>0.05). Conclusion: Given there is no predisposition to thrombophilia and IgAV is a form of vasculitis, the cause of thrombosis among patients with IgAV may involve mechanisms related to the inflammationhemostasis cascade.